Sustaining Teacher Education During COVID-19: Challenges with Remote Teaching and Learning Faced by Preservice Mathematics Teachers - Rabaza, Msebenzi; Enu, Justice; Ngcobo, Zanele Annatoria; Jhagroo, Jyoti (Wiley, 2024)
Education institutions worldwide implemented remote teaching and learning to ensure the sustainability of their academic programmes and continuity of study. However, evidence from the literature revealed that remote teaching and learning posed challenges to teaching and learning. This study seeks to explore whether there is a relationship between remote teaching and learning and the challenges faced by preservice mathematics teachers when learning mathematics education during COVID-19. It focuses on remote teaching at four universities: two in South Africa, one in Ghana, and one in New Zealand. The study design followed a quantitative research approach, with 95 preservice mathematics teachers from the four universities randomly assigned to complete an online survey after signing informed consent forms. This study revealed two challenging factors facing preservice mathematics teachers during remote teaching and learning: data, and technological devices for learning. The findings revealed no significant difference (p < 0.000) between remote teaching and learning and the challenges faced by preservice mathematics teachers when learning during the COVID era. Therefore, the null hypothesis is rejected, since p < 0.05. This study concludes that a significant relationship exists between accessibility to technological devices for learning as a challenge to preservice teachers and remote teaching and learning during COVID-19. It is recommended that appropriate technological devices are provided to assist preservice teachers to study mathematics education, thus ensuring continuing access to quality education.
Keywords: Environmental Sciences